2006
DOI: 10.1590/s1806-83242006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Activity, distribution and regulation of phosphofructokinase in salivary gland of rats with streptozotocin-induced diabetes

Abstract: Although the influence of diabetes on salivary glands is well studied, it still presents conflicting results. In this work, the regulation of the phosphofructokinase-1 enzyme (PFK-1) was studied utilizing the salivary glands of rats. Diabetes was induced by a single intraperitoneal injection of streptozotocin (60 mg/Kg of body weight) in rats (180-200 g). The animals were killed 30 days after the induction of diabetes and the submandibular and parotid salivary glands were used. Hyperglycemia was evaluated by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
1
9
0
7
Order By: Relevance
“…Experimental animal models of diabetes induced by either alloxan or streptozotcin (STZ) have been used to study aspects of the pathophysiology of this disease. Previous papers from our laboratory showed that STZinduced diabetic rats had some biochemical parameters altered in the salivary glands [14][15][16] . It has been reported that a prolonged elevation of blood glucose in diabetes mellitus may be responsible for an overall increase in the degree of proteins glycation.…”
Section: Introductionmentioning
confidence: 96%
“…Experimental animal models of diabetes induced by either alloxan or streptozotcin (STZ) have been used to study aspects of the pathophysiology of this disease. Previous papers from our laboratory showed that STZinduced diabetic rats had some biochemical parameters altered in the salivary glands [14][15][16] . It has been reported that a prolonged elevation of blood glucose in diabetes mellitus may be responsible for an overall increase in the degree of proteins glycation.…”
Section: Introductionmentioning
confidence: 96%
“…[2][3][4][5][6] Experimental animal models of diabetes, induced either by alloxan or streptozotocin, have been used to study aspects of the pathophysiology of this disease. In salivary glands alterations in the glycolytic enzymes activities, 7,8 antioxidant parameters 9,10 of the salivary glands have been reported. It has been reported that a reduction in submandibular salivary flow rate of rats was associated with calcium signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is widely known that several diseases could affect salivary gland function and saliva secretion. In particular, diabetes mellitus (DM) has been the focus of many studies using major salivary glands, attempting to elucidate the changes in the activity of some pivotal enzymes of the glycolytic pathway (hexokinase and phosphofructokinase 1) and glycogen (glycogen synthase and glycogen phosphorylase) metabolism …”
Section: Introductionmentioning
confidence: 99%